The causal effect of education on tooth loss: evidence from united kingdom schooling reforms - Matsuyama, Yusuke; Jürges, Hendrik; Listl, Stefan (American journal of epidemiology, 2019)
Abstract. Associations between education and oral health have frequently been reported, but until now there has been no causal evidence. Exploiting exogenous v